London falling [compact disc, unabridged] : a mysterious death in a gilded city and a family's search for truth - Keefe, Patrick Radden, 1976- (Penguin Random House, 2026)
A family devastated by the sudden death of their nineteen-year-old son discovers that he had created a secret life which drew him into the dangerous criminal underworld that lies beneath London's glittering surface.